(untitled) - Pfeffer, Susan Beth (Lincolnwood, 2000)
In 1923, Alicia Martinez, living with Los Angeles oil millionaires, is thrilled to be cast in Revenge of the Aztecs, an epic film being produced in Hollywood by her best friend's father. When idols topple, rocks roll down hilss, and other mysterious events occur, Alicia must find out if these happenings are just accidnets or if she is the target of a criminal plan that threatens the completion of the movie as well as her safety. If they are not accidents, who is behind them? Could it be someone Alicia has loved and trusted for years? And if it is, can Alicia ever trust again? Jamestown’s American Portraits explores the growth of different generations and cultures through the lives of young boys and girls. These titles are told from a diverse group of boys and girls, coming from different and unique backgrounds that represent America’s own diverse population, spanning from the Jamestown Settlement to the Civil Rights Movement.
Keywords: American fiction